Consumer Perception Towards Shopping Malls : Evidence from a Tier II City - Khanna, Pooja; Seth, Suresh (Indian Journal of Marketing, 2018)
The concept of shopping malls in India is undergoing a tremendous change. Having attained maturity in tier I cities, these malls are treading onto tier II and tier III cities with positive anticipation. Retailers see a greater scope for growth in these cities. Pressurized by sky - high real estate prices, immoderate rentals, inflated development costs, and low foot-falls, retailers are shifting to tier-II and tier - III cities. Turning these malls into a profitable venture will be a great challenge in the foreseeable future. Mall developers and retailers need to understand the psychology of consumers and gain a deep insight into the factors which give them satisfaction. This study attempted to analyse the factors that had an impact on consumers shopping in malls in a tier-II city. Use of exploratory factor analysis revealed that Aesthetic Ambience, Physical Infrastructure, Hedonic Factors, Service and Convenience, Escape/Stress Relieving, Promotional Offers, Merchandize, Shopping Enjoyment, and Excitement were the most important factors influencing customers’ perception about shopping malls. The results of regression analysis further revealed that Enjoyment, Promotional Offers, Hedonic Factors, Stress Relieving, and Excitement had a considerable impact on customer perception about shopping malls in a tier II city.